Research methods in biomechanics - Robertson, D. Gordon E. 1950-; Caldwell, Graham E. 1954-; Hamill, Joseph 1946-; Kamen, Gary; Whittlesey, Saunders N. (Human Kinetics, 2014)
In the highly technical field of biomechanics, research methods are frequently upgraded as the speed and sophistication of software and hardware technologies increase. This second edition features more than 100 new pieces of art and illustrations and chapters introducing various techniques and areas of research